Implementasi Pendidikan Karakter Melalui Pembelajaran Tematik dalam Membentuk Sikap Sosial dan Tanggung Jawab Siswa - Sefida Fitriani; Heri Maria Zulfiati (LP2M Universitas Sarjanawiyata Tamansiswa, 2021)
This research aims to describe the implementation of character education social attitude and responsibility through thematic learning. The supporting and inhibiting factors, the solution in overcoming the obstacles. The method of this research is qualitative descriptive. This research subjects are headmaster, teacher, and four third grade students. The data collection technique are obtained through observation, interview, and documentation. The technique of qualitative data analysis uses interactive model. The result of research showed that third grade of SD N Jaranan Bantul Yogyakarta has implemented social attitude and responsibility. The implementation social attitude could be seen from students have maintained harmony, have worked honestly on individual assignment, have obeyed the rules, have completed the assignment well, always respect to teacher and want to help their friends, are brave to express their opinions. While, the implementation of students responsibility could be seen on the students have carried out class pickets, active role in the school activity, and proposed a problem solution. The supporting is namely teacher role model, adequate school infrastructure, and government has promoted character education. The inhibiting factors are character, background, and different ability of students, students lack of understanding the implementation of social attitude and responsibility and parents less concern with students. The solution are to provide the guidance, advice, and give reprimand to students, students ask for character values that they have not understand, and teachers communicate with student’s parents.